In vitro cytotoxicity and antibiotic application of green route surface modified ferromagnetic TiO2 nanoparticles. Issue 23 (30th April 2019) - Atique Ullah, A. K. M.; Tamanna, A. N.; Hossain, A.; Akter, M.; Kabir, M. F.; Tareq, A. R. M.; Fazle Kibria, A. K. M.; Kurasaki, Masaaki; Rahman, M. M.; Khan, M. N. I.
Abstract : Artocarpus heterophyllus leaf extract mediated green synthesized TiO2 nanoparticles exhibit less toxicity with high antibacterial activity. Abstract : The enormous numbers of applications of TiO2 nanoparticles (NPs) cause concern about their risk to the environment and human health. Consequently, motivated by the necessity of searching for new sources of TiO2 NPs of low cytotoxicity with antibacterial activity, we synthesized TiO2 NPs by a green route using a solution of titanium(iv ) isopropoxide as a precursor and an aqueous extract of Artocarpus heterophyllus leaf as a reducing and surface modifying agent. We investigated their structure, shape, size, and magnetic properties, and evaluated their antibiotic application and cytotoxicity. The synthesized TiO2 NPs were applied against two Gram-negative bacteria ( E. coli and S. typhimurium ) and two Gram-positive bacteria ( S. aureus and B. subtilis ) to observe their antibacterial activity; and eventually clear zones of inhibition formed by the TiO2 NPs were obtained. Moreover, after exposing the synthesized TiO2 NPs to HeLa cells (carcinoma cells) and Vero cells (normal cells), no toxic effect was found up to a dose of 1000 mg L −1, indicating the safe use of the samples up to at least 1000 mg L −1 . However, toxic effects on HeLa cells and Vero cells were observed at doses of 2000 mg L −1 and 3000 mg L −1, respectively. These results indicate the safe use of Artocarpus heterophyllus leaf extract mediated synthesized TiO2 NPs in their potential applications.